Water hyacinth ponds as an alternative to polishing ponds for the treatment of effluent for UASB - Srivastava, Kamna (My University, 2013)
Urban air pollution, primarily in the form of highly elevated ambient concentrations of small particulate matter, poses a serious threat to the health of urban dwellers in many countries. India, a developing country, is one of the first ten industrial countries of the world. Because of the enhanced anthropogenic activities, India is one of the most polluted country in the world. Various sources reveal that Mandi Gobindgarh and its surrounding areas are polluted with regard to Air pollution, which exceeds the national ambient air quality standards (NAAQS). Mandi Gobindgarh is one of the critically polluted areas with regard to air pollution as designated by CPCB. Air is excessively hot and dry due to furnaces. Air pollution in Mandi Gobindgarh is mainly caused by three sources, namely, industrial, stubble burning and vehicular emissions. Open biomass burning of crop residue is a common practice after harvesting, this activity releases a large amount of air pollutants, which can cause serious effects on the ambient air quality, public health and climate. In crop residue burning there is no stack, no vent or duct, thus all emissions are fugitive. The effect of pollution is much lesser pronounced in rural areas than in urban areas. However the sickness increases in rural areas during paddy and wheat chaff burning due to toxicity of the gases from chaff. In this study, ground-based ambient air monitoring was conducted at five different locations in Mandi Gobindgarh, Punjab, in order to determine the impact of open burning of crop residues on concentration levels of particulate matter (PM10 and PM2.5). A study was carried out for the measurement of PM10 and PM2.5 for one rice crop season from October 2012 to January 2013 and one wheat crop season from March 2013 to May 2013, using Respirable Dust Sampler. Levels of PM10 and PM2.5 showed increase of 86.65% and 53.2% respectively during the rice crop residue burning months, and an increase of 60.4% and 33.1% respectively during wheat crop residue burning months, at an agricultural site. Whereas, an increase of 33.33% and 31.1% respectively during the rice crop residue burning months, and an increase of 23.7% and 9.5% respectively during wheat crop residue burning months, at an Industrial site, where agricultural impact is minimal and at a site with maximum vehicular emission, there was an increase of 33.6% and 25.8% respectively during rice crop residue burning months and an increase of 29.1% and 28% respectively during wheat crop residue burning months.
M.Tech (EST) Dissertation
Keywords: Water hyacinth; UASB; polishing pond